Correlation and Influencing Factor Analysis Between Gal-3 and Recurrent Patients With Nonvalvular Atrial Fibrillation After Radiofrequency Ablation - Jing Lu; Fan Yang; Yu Gao; Ruijuan Li; Runqin Li; Nan Zhang; Yan Ren; Dengfeng Ma (Cardiovascular Therapeutics)
Conclusion: Elevated Gal-3 and hs-CRP levels along with increased LAV are predictive of AF recurrence, irrespective of AF type. This finding holds a significant potential for guiding therapeutic strategies in clinical practice.